Analysis of Idiomatic Expressions Used in the Novel "Alice's Adventures in Wonderland" - Putri Dwi Maharani; Lina Meilinda (Jurnal Bahasa Inggris Terapan, 2025)
This research entitled Analysis of Idioms Used in Alice's Adventures in Wonderland aims to identify idioms, classify them into idiom types based on Lim's (2004) theory, classify the clues used to guess the idiom meanings, and analyse the meaning from the context. The object of this research is a novel by Lewis Carroll entitled Alice's Adventures in Wonderland. The subject of this research is idioms. The result shows that there are 113 idioms categorised into 6 types of idioms, including phrasal verb idioms, prepositional phrase idioms, idioms with verbs as keywords, idioms with nouns as keywords, idioms with adjectives as keywords, and idiomatic pairs. The type of idioms with nouns as keywords is the most widely used with 45.1% of the total. The idioms that have been identified are then interpreted using 2 clues, namely linguistic and non-linguistic. Most of the idioms were identified using linguistic clues with 81%. Some idiom dictionaries are used as linguistic clues, while non-linguistic clues consider idioms based on cultural aspects, situations, experiences, and habits. The interpretation of the meaning is then adjusted to the context of the story in the novel.